EFEKTIVITAS METODE DRILL DALAM PEMBELAJARAN TAFSIR AMALY DI MA AL-URWATUL WUTSQO JOMBANG - Khudriyah; Nur Amalia, Dona (ILJ: Islamic Learning Journal, 2023)
Learning Tafsir Amaly is very important because it contains details and studies of important verses in the Qur'an. However, in practice the teacher used a method that is not appropriate, so that students were easily bored in the learning process, therefore a new method of teaching is needed.This research is aimed to know whether or not drill method influenced the students Tafsir Amaly achievement. The research used experimental design belongs to comparative study with a survey approach. The samples of this research were taken from students of MA al Urwatul Wutsqo. The findings of this research result showed that the t accounted is higher than t table (6. 529 < 2. 00324), with degree of freedom is 56 and degree of significance is 0, 05, and sig. 0.000 < 0.05. it can be concluded that drill method is effective to teach Tafsir Amaly at MA al Urwatul Wutsqo.